2015
DOI: 10.4012/dmj.2015-024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peri-implant bone formation around injection-molded and machined surface zirconia implants in rabbit tibiae

Abstract: The aim of this study was to compare osseointegration and surface characteristics of zirconia implants made by the powder injection molding (PIM) technique and made by the conventional milling procedure in rabbit tibiae. Surface characteristics of 2 types of implant were evaluated. Sixteeen rabbits received 2 types of external hex implants with similar geometry, machined zirconia implants and PIM zirconia implants, in the tibiae. Removal torque tests and histomorphometric analyses were performed. The roughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Nevertheless, even with these advantages, the authors have reported some clinical drawbacks, such as sensitivity to Ti, electrical conductivity, corrosive properties, accumulation of metal ions and esthetic problems as a result of their dark‐grayish coloring, which have led researchers and clinicians to explore alternatives . Therefore, zirconia (ZrO 2 ) implants containing tetragonal polycrystalline yttria (Y 2 O 3 ) (Y‐TZP) have been proposed as an alternative to Ti because of its esthetic benefits, superior mechanical properties to other ceramic biomaterials and high biocompatibility in vitro and in vivo . Taken together, the available data indicate that zirconia could be a suitable substitute for Ti, but few studies support its clinical use .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, even with these advantages, the authors have reported some clinical drawbacks, such as sensitivity to Ti, electrical conductivity, corrosive properties, accumulation of metal ions and esthetic problems as a result of their dark‐grayish coloring, which have led researchers and clinicians to explore alternatives . Therefore, zirconia (ZrO 2 ) implants containing tetragonal polycrystalline yttria (Y 2 O 3 ) (Y‐TZP) have been proposed as an alternative to Ti because of its esthetic benefits, superior mechanical properties to other ceramic biomaterials and high biocompatibility in vitro and in vivo . Taken together, the available data indicate that zirconia could be a suitable substitute for Ti, but few studies support its clinical use .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the significant hardness of zirconia implants makes the process of surface roughening very difficult and, in some cases, may compromise strength . Although Y‐TZP has genuine potential to become an effective implant material, it should be continuously tested to consolidate its true advantages and disadvantages in vivo …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…,Chang, Oka, Nakamura and Gu (1996),Chung, Kim, Shon and Park (2013),Han et al (2016),Hayashi, Inadome, Tsumura, Mashima and Sugioka (1993),Hayashi, Matsuguchi, Uenoyama and Sugioka (1992),Kim et al (2015),Mai et al (2012),Ratiu, Cavalu, Miclaus, Rus and Lazarescu …”
mentioning
confidence: 99%